Surface Application of Paper Chemicals - Brander, James (Springer Netherlands, 1997)
This book examines the chemicals used in the surface treatment of paper products, the means used to apply them, and the product characteristics they are intended to enhance. The emphasis of this book is placed on the technologies for 'on-machine' surface treatment (i.e. on the paper machine) rather than separate coating operations. Accordingly, the book includes a comprehensive tretment of metered size press technology from one of the foremost manufacturers and the chapters describing the chemicals used are biased towards on-machine application. Similarly, the product areas that are particularly discussed are two of those where development effort into effort into on-machine applications is the most intense-non-impact printing papers and food grade board (often made from 100%recycled base. There is extensive discussion of how the different chemicals used in in the surface treatment can interact, both with one another and in some circumstances, even with those used in the bulk treatment especially sizing). Suggestions on avoiding these interactions are made and examples are given. The book ends with a discussion of the impact of surface treatment on the recycling of papers treated in various ways. Though written principally for technologists in paper mills, this book is essential reference source for chemical and equipment suppliers and for research staff in academic and technical institutes.